2023
DOI: 10.3390/vaccines11010190
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of SARS-CoV-2 Vaccine Uptake among Health Professionals: A Cross-Sectional Study in Ghana

Abstract: COV-2 SARs has disproportionately affected low- and middle-income countries such as Ghana, where the healthcare system was not prepared enough to provide care, drugs, and equipment. This study was carried out to assess predictors of COVID-19 vaccine acceptance among health professionals in the Bono region of Ghana. A facility-based cross-sectional study was conducted among 424 health professionals recruited through simple random sampling. Univariate and multivariate logistic regression models were utilized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Freeman et al [39](2022), there is evidence suggesting that hesitancy is more prevalent among those who identify as female, have lower income levels, and belong to certain ethnic groups. Adverse side effects of the vaccines [9], [13], [15], [26], [28], [30], [32], [42] 8 2 Mistrust in the vaccine [8], [32], [37], [42],[43] 5 3…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…It is crucial to recognize that demographic factors such as employment status, rural or urban residency, occupation, level of experience, and political party affiliation among opposition voters were not extensively examined in the assessment of factors influencing COVID-19 vaccine acceptance and hesitancy in Ghana (see Figure 4). [5], [8], [11], [13], [27], [34], [37], [49], [44] 9 Gender [6], [8], [11], [30], [35], [37], [42], [44] 8 Religion [8], [13], [15], [27], [34] [42], [44], [49] 8 Age [9], [11], [15], [27], [42], [49] 6 Marital Status [12], [37], [42] 3 Primary source of information about COVID-19 vaccine [11], [13], [44] 3 According to Backhaus [50], urban residency and current pregnancy were significantly and positively associated with refusing vaccination against COVID-19, whereas age, savings, and using contemporary contraceptives were significantly and negatively associated with refusing vaccination. Additional research by Hwang et al [51] indicates that younger age, lack of religious affiliation, political conservatism, and lower family income are also substantially associated with vaccine hesitancy.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations